2017
DOI: 10.1590/0100-69912017005007
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancer surgery in patients operated on an emergency basis

Abstract: Objective: to study the epidemiological profile of patients with colorectal cancer operated on an emergency basis at the Bonsucesso Federal Hospital. Methods: this is a retrospective study of patients operated between January 1999 and December 2012. We analyzed the following variables: age, gender, clinical data, TMN staging, tumor location, survival and types of surgery. Results: we evaluated 130 patients in the study period. The most frequent clinical picture was intestinal obstruction, in 78% of cases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
(22 reference statements)
0
6
0
1
Order By: Relevance
“…Antony et al have concluded after risk adjustment that urgent surgery in colon cancer has no impact on survival [ 52 ]. On the other hand, Ramos et al claimed that there was a high mortality rate and a low survival rate in colorectal cancer patients operated on urgently [ 53 ]. Smothers et al claimed that emergency surgery has a strong negative influence on immediate surgical morbidity and mortality; however, other coexistent factors, such as advanced disease, the age of the patient, and medical comorbid conditions, may also influence these outcomes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antony et al have concluded after risk adjustment that urgent surgery in colon cancer has no impact on survival [ 52 ]. On the other hand, Ramos et al claimed that there was a high mortality rate and a low survival rate in colorectal cancer patients operated on urgently [ 53 ]. Smothers et al claimed that emergency surgery has a strong negative influence on immediate surgical morbidity and mortality; however, other coexistent factors, such as advanced disease, the age of the patient, and medical comorbid conditions, may also influence these outcomes [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instant management is needed for acute complete OCC (COCC). Recommended treatments are different according to tumor location ( 1 , 2 , 4 6 , 18 , 19 ). According to 2017 WSES guidelines on colon cancer obstruction, for right COCC, right colectomy with primary anastomosis is a preferred treatment option ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the strength of this study was that it only included non-emergent obstructive colon cancer cases. Thus, morbidities in an emergent situation would not affect survival ( 4 6 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Hartmann procedure was initially indicated for complicated tumors of the descending colon [ 12 ] but then was questioned because of its association with an increased risk of postoperative morbidity [ 13 ]. However, for other authors, the Hartman procedure remains an applicable option for the majority of patients with emergency surgery for left colon cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%